If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -17 = -2x Combine like terms: 15 + -17 = -2 -2 = -2x Solving -2 = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -2 + 2x = -2x + 2x Combine like terms: -2x + 2x = 0 -2 + 2x = 0 Add '2' to each side of the equation. -2 + 2 + 2x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 0 + 2 2x = 0 + 2 Combine like terms: 0 + 2 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 9x+5-3=2x+16 | | -63/7-1=7 | | 7/7-1=7 | | 56/7-1=7 | | 4+x=-11+9 | | 0/7-1 | | 0.10d+0.25q=8.65 | | 0/7-1=7 | | 7x^2/3-14=0 | | -27=5-4*8 | | 4(x-1)-2x=0 | | -27=5-4*-6 | | 8=-17+z | | -27=5-4*4 | | -27=5-4*-1 | | 9(-5-8)=-54 | | 9(6-8)=-54 | | 9(-8-8)=-54 | | q/13=0 | | m^2+11+30=0 | | 1/12y^2-5/7y | | c-17=3 | | 4x-(x+8)=9x+8+1 | | 17u-9u=56 | | C^2-6cx-40x^2= | | 8+3w=-1 | | fx=x^2+2 | | 42t-42=61t-80 | | g(x)=2f(x)+6 | | 0.4x+4.3=3.7 | | 261=-2v-5(1-8v) | | 4(2-x(x+1))+2(-4+x)=5(x+19)-4x(x+2) |